Application of targeted high-throughput sequencing as a diagnostic tool for neonatal genetic metabolic diseases following tandem mass spectrometry screening - Lai, Guihua; Gu, Qiying; Lai, Zhiyong; Chen, Haijun; Tu, Xiangwen; Chen, Junkun; Huang, Jungao (Frontiers in Public Health, 2024)
BackgroundTandem mass spectrometry (MS/MS) is a crucial technique for detecting inborn errors of metabolism (IEM) in newborns. However, the high false positive rate poses challenges in diagnosing specific types of diseases. Therefore, this study aimed to evaluate the role of targeted next-generation sequencing (NGS) in the accurate diagnosis of positive samples identified through MS/MS screening.MethodsA cohort study of 260,915 newborns was conducted from January 2018 to June 2023 in Ganzhou City, southern China. Heel blood samples were collected within 72 h of birth and subjected to MS/MS analysis. Infants with positive MS/MS results underwent targeted NGS to confirm the diagnosis and identify genetic variants.ResultsAmong 1,265 suspected cases with positive MS/MS results, 73 were confirmed by NGS, and 12 were identified as carriers of recessive diseases. The overall incidence rate was 1 in 3,574, effectively ruling out 94.2% (1,192/1,265) of the MS/MS false-positive. We found 76 variants in 18 genes associated with 15 types of IEM. Among these, 64.47% (49/76) were pathogenic, 10.53% (8/76) were likely pathogenic. Remarkably, 7.89% (6/76) were identified as novel variants. Variants in SLC22A5 (NM_003060.4) gene was most prevalent, accounting for 41% (77/188), with hotspot variants including c.51C > G, c.1400C > G, and c.338G > A.ConclusionTargeted NGS technology can serve as a crucial diagnostic tool for neonatal genetic metabolic diseases following MS/MS screening. Additionally, we identified IEM variant hotspots and some novel variants in our region, which are the underlying causes of disease in patients with IEM.